1994
DOI: 10.1111/j.1526-100x.1994.tb00067.x
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass Planting in the Southeastern United States: Methods for Accelerating Habitat Development

Abstract: Seagrass transplanting experiments were conducted in Back Sound, Carteret County, North Carolina, and Tampa Bay, Pinellas County, Florida. In Florida, we compared three planting methods (cores, stapled bare root, and peat‐pot plugs) for shoot addition rate coverage, and labor cost (harvest, fabrication, and deployment) using Halodule wrightii. Only planting methods and development rates were recorded for Syringodium filiforme. Fertilizer additions were made to peat‐pot plantings of H. wrightii and Zostera mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 10 publications
1
55
0
2
Order By: Relevance
“…Late season plantings, although not the optimal period of seagrass growth, may be outside the peak in bioturbation, thereby enhancing survival and persistence of plantings. Similarly, Fonseca et al (1994) found that bioturbation exclosure cages greatly improved spnngtime planting survival at our most disturbance-prone site, Coffeepot Bayou. Our surveys of PU survival based on averages among randomly located 1 m2 plots revealed that for plots which eventually established persistent cover, 66% PU survival occurred (Table 2).…”
Section: Seagrass Morphometricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Late season plantings, although not the optimal period of seagrass growth, may be outside the peak in bioturbation, thereby enhancing survival and persistence of plantings. Similarly, Fonseca et al (1994) found that bioturbation exclosure cages greatly improved spnngtime planting survival at our most disturbance-prone site, Coffeepot Bayou. Our surveys of PU survival based on averages among randomly located 1 m2 plots revealed that for plots which eventually established persistent cover, 66% PU survival occurred (Table 2).…”
Section: Seagrass Morphometricsmentioning
confidence: 99%
“…We attempted to evaluate the rate of flonstic development in planted beds of Halodule wrjghtii, Syringodium fillforme and mix- species (Fonseca et al 1987) 1 mine which aspects of the seagrass itself would be the most useful in assessing planting projects (Fonseca 1989(Fonseca , 1992(Fonseca , 1994 while exploring the dynamics of seagrass beds in Tampa Bay, Flonda, USA. We measured several attributes of seagrass beds commonly reported on in the literature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Excess inorganic nitrogen can contribute to reduced light conditions or smothering by macroalgae (Costa et al 1992, Short et al 1995. Additionally, bioturbation has been shown to be a factor that can greatly reduce the survival and expansion of both naturally occurring (Suchanek 1983, Philippart 1994 and transplanted (Harrison 1987, Fonseca et al 1994, 1996, Philippart 1994, Molenaar & Meinesz 1995) seagrass.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Bioturbation, often causing transplantation losses along the eastern and southern shores of the USA (Fonseca et al 1994, Davis et al 1998, Hammerstrom et al 1998, had no effects on the transplantations in the Dutch Wadden Sea (see 'Introduction'). This was further evidenced by our finding that the plants disappeared also in enclosures without tops (0 to 5% reduced water dynamics, entrance of large animals unlikely and not observed), half of the plants disappeared in exclosures with gauze tops (40 to 50% reduced water dynamics, no animals larger than 1 mm could enter), whereas all plants remained in the plexiglass-topped exclosures (80 to 100% reduced water dynamics).…”
Section: Water Dynamicsmentioning
confidence: 99%
“…m -2 (Davis et al 1998), are only present in much lower densities than this in intertidal areas of the Wadden Sea (van der Veer et al 1998, Dittmann & Villbrandt 1999. Rays, potentially damaging to eelgrass transplantations (Fonseca et al 1994), are nowadays absent from the Wadden Sea (Lozán et al 1994, Rijnsdorp et al 1996. Most of the other sediment-disturbing animals (e.g.…”
Section: Introductionmentioning
confidence: 99%